The effects of VAR implementation in the Turkish Football Super League - Sucular, E.; Göral, K. (Turkish Journal of Sport and Exercise, 2025)
Technological advances have significantly impacted the field of sport, revolutionizing various aspects of training, performance analysis and supporter participation. The development of data analysis systems, especially in football, has been particularly influential in recent times. One of the latest technologies to enter our lives in football is the Video Assistant Referee (VAR) system. The implementation of technologies such as the VAR system has aimed to reduce errors and increase the accuracy of referees' decisions, emphasizing the importance of their role in the application of the rules of the game. For this reason, according to the variable of being the home team; when the first decisions made by the referee before the VAR system was activated and the decisions made after the VAR system was activated in the positions where the VAR system was activated; Would there be an advantage to the home team in the decisions made by the referee if there was no VAR system? As a result of the analysis related to this question; in 243 positions (49.7%), the home team had an advantage while in 246 positions (50.3%) the away team had an advantage. There was no statistically significant difference (p>0.05) when it was analyzed whether the advantage given to the home team or the advantage given to the away team was dependent on the season variable. In 489 positions where the VAR system was activated, it was observed that without VAR, full stands, pitch advantage or noise did not provide an advantage to the home team in wrong refereeing decisions.